Sport and health - Bakashvili, V. G. (Національний технічний університет "Харківський політехнічний інститут", 2025)
Physical activity is a natural need of a person. The development of the entire sphere of social activity is impossible without physical culture. The human need to satisfy physical activity is the driving force of the development of physical culture, in which the factor of maintaining and strengthening health is decisive. Health, as the highest value, is the main category that determines the content of the phenomenon.
Keywords: sport; health; physical activity; human needs; strengthening health; general culture of society; working capacity